Differential Hemodynamic Effects of Exercise and Volume Expansion in People With and Without Heart Failure. (January 2015) - Andersen, Mads J.; Olson, Thomas P.; Melenovsky, Vojtech; Kane, Garvan C.; Borlaug, Barry A.
<x xml:space="preserve">Abstract</x> Background— Invasive hemodynamic exercise testing is commonly used in the evaluation of patients with suspected heart failure with preserved ejection fraction (HFpEF) or pulmonary hypertension. Saline loading has been suggested as an alternative provocative maneuver, but the hemodynamic changes induced by the 2 stresses have not been compared. Methods and Results— Twenty-six subjects (aged, 67±10 years; n=14 HFpEF; n=12 control) underwent right heart catheterization at rest, during supine exercise, and with acute saline loading in a prospective study. Exercise and saline each increased cardiac output and pressures in the right atrium, pulmonary artery, and pulmonary capillary wedge positions. Changes in heart rate, blood pressure, rate–pressure product, and cardiac output were greater with exercise compared with saline. In controls subjects, right atrial pressure, pulmonary arterial pressure, and pulmonary capillary wedge pressure increased similarly with saline and exercise, whereas in HFpEF subjects, exercise led to ≈2-fold greater increases in right atrial pressure (10±4 versus 6±3 mm Hg; P=0.02), pulmonary arterial pressure (22±8 versus 11±4 mm Hg; P=0.0001), and pulmonary capillary wedge pressure (18±5 versus 10±4 mm Hg; P<0.0001) compared with saline. Systolic reserve assessed by stroke work and cardiac power output was lower in HFpEF subjects with both exercise and saline. Systemic and pulmonary arterial compliances were enhanced with saline but reduced with exercise. Conclusions— Exercise elicits greater pulmonary capillary wedge pressure elevation compared with saline in HFpEF but not controls, suggesting that hemodynamic stresses beyond passive stiffness and increased venous return explain the development of pulmonary venous hypertension in HFpEF. Exercise testing is more sensitive than saline loading to detect hemodynamic derangements indicative of HFpEF. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01418248.